Distance, environmental and substrate factors impacting recovery of bryophyte communities after harvesting. Issue 1 (31st October 2017) - Baker, Thomas P.; Jordan, Gregory J.; Fountain‐Jones, Nicholas M.; Balmer, Jayne; Dalton, Patrick J.; Baker, Susan C.
Abstract: Aims: Bryophyte re‐colonization after disturbance is largely governed by environmental conditions within disturbed forests. In particular, distance to a forest edge is an important predictor of bryophyte community re‐colonization, through either direct constraints, such as dispersal limitation, or indirectly by altering environmental conditions. This study examines a range of factors – environmental, distance to an edge, substrate specific environment or local‐level environment – to determine which are important in the re‐colonization of bryophyte communities after forest harvesting. As bryophyte communities vary with the particular substrate inhabited, responses were examined across four substrates (rock, exposed roots, ground and CWD). Location: Tasmanian southern forests, Australia. Methods: Bryophyte composition was examined on four substrates (ground, coarse wood debris, exposed roots, rocks) within three ages (~7, ~27 and ~45 years post‐disturbance) of harvested wet eucalypt forest. Re‐colonization success of bryophyte communities was determined by comparing communities in regeneration forest to mature forest communities using axis scores from one‐dimensional constrained ordination. The importance of various environmental conditions for re‐colonization success was then modelled. Finally, path analysis was used to determine whether the impact of distance to a forest edge was meditated through its effects on key environmental variables. Results: Multiple environmental factors impacted re‐colonization of mature bryophyte communities. Local‐level conditions such as microclimate (temperature, humidity and VPD) and LAI were the most important in determining re‐colonization across substrates. Path analysis showed that distance to a forest edge had a significant impact on re‐colonization success, but only a relatively small part of this was mediated through its impact on environmental factors. Conclusions: Bryophyte re‐colonization is driven by a combination of microclimate conditions and factors related to distance from a forest edge (most likely dispersal distance). While some substrate‐specific factors impact bryophyte re‐colonization success, the consistent impact of local environmental factors across substrates suggests that harvesting management strategies that develop more 'mature' microclimate conditions and increase proximity to nearby mature forest patches will be beneficial for all bryophytes communities. As bryophyte re‐colonization was correlated with temporally dynamic environmental conditions, we suggest that forest age needs to be considered in future work. Abstract : Bryophyte recolonisation post‐disturbance is governed by multiple environmental factors. We show that microclimate conditions and distance to a standing forest are two critical factors impacting bryophyte recolonisation. Additionally, both factors are influential across a range of substrates suggesting that management techniques which reduced dispersal distance andminimise microclimate extremes will help recolonisation across multiple bryophyte communities.